NURSING SCIENCE: THE DNP PRACTICE BASIS - Fahad Jubjub Ali Aldhafeeri, Majed Mutairan Saud Aljohani, Abdulaziz Ibrahim Alanazi, Khaled Ebrahem Alenzi, Hala Abdulrazaq Alanzi, Abdullah Thunayyan Kamin Aldhafeeri, Meshal Suwayyid Alanazi, Fawaz Muzahim Alshammari,; Fawzia Awad Mukhlid Al-Mutairi, Aljawharaha Habeb Al-Mutairi, Hamidah Ahmed Howaish Alanazi, Mamdouh Mohammed Alshammari, Khlood Sawyer Ali Alinazi, Hasna Mohammed Alshammari, (Chelonian Research Foundation, 2022)
The importance of nursing science and theory for doctor of nursing practice (DNP) graduates is examined in this chapter. A lot of DNPs prioritize efficacy in practice and have a pragmatic perspective on nursing. The chapter makes the case that DNPs must have a solid background in nursing science in order to go beyond a simply practical approach. It highlights the distinct viewpoint that nursing science contributes to healthcare by examining the ways in which DNPs apply scientific theories and concepts at the bedside. The importance of DNPs as nurse scientists and their contribution to the continuous advancement of nursing knowledge is emphasized in the chapter's conclusion. Key words: Nursing philosophy, evidence-based practice, advanced nursing practice, nursing science, Doctor of Nursing Practice (DNP)